2000
DOI: 10.1083/jcb.148.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-Dependent Cdk Activity Is a Requisite Effector of Apoptotic Death Events

Abstract: The caspase-dependent activation of cyclin-dependent kinases (Cdks) in varied cell types in response to disparate suicidal stimuli has prompted our examination of the role of Cdks in cell death. We have tested the functional role of Cdk activity in cell death genetically, with the expression of dominant negative Cdk mutants (DN-Cdks) and Cdk inhibitory genes. Here we demonstrate that Cdk2 activity is necessary for death-associated chromatin condensation and other manifestations of apoptotic death, including ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
1
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 105 publications
(158 reference statements)
3
70
1
1
Order By: Relevance
“…A previous study has shown that CDK2 is upstream of caspases (Hakem et al, 1999). Others have shown that CDK2 is downstream of caspases (Harvey et al, 2000;Levkau et al, 1998). Thus, the role of CDK2 may depend on the cell type and/or the nature of the apoptotic stimulus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study has shown that CDK2 is upstream of caspases (Hakem et al, 1999). Others have shown that CDK2 is downstream of caspases (Harvey et al, 2000;Levkau et al, 1998). Thus, the role of CDK2 may depend on the cell type and/or the nature of the apoptotic stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that caspase-3 is upstream of CDK2 (Hakem et al, 1999), yet others have shown that caspase-3 is downstream of CDK2 (Harvey et al, 2000;Levkau et al, 1998). To determine if active cytoplasmic CDK2 was proximal to the activation of caspase-3, caspase-3 activity was measured in UV irradiated cells in the presence and absence of the CDK2 inhibitor, Roscovitine.…”
Section: Cyclin A-cdk2 Is Upstream Of Caspase-3 In the Apoptotic Pathwaymentioning
confidence: 99%
“…The effects of small molecule inhibitors can be mimicked by naturally occurring small inhibitor proteins, such as p21 cip1 , p27 kip1 , and p16 ink4 , which can inhibit the activity of CDK2 (Coqueret, 2003) and block apoptosis in HeLa cells (Harvey et al, 1998), in fibroblasts (Hiromura et al, 1999) and in differentiating myocytes (Wang and Walsh, 1996). Additional supportive experimental evidence for the role of CDK activity in apoptosis comes from studies that use 'kinase dead' mutants of CDK1 or CDK2 (Meikrantz and Schlegel, 1996;Harvey et al, 2000;Castedo et al, 2002b). Finally, the FT210 murine cell line, which harbours a temperature sensitive mutation in the CDK1 gene, will not enter apoptosis when cultivated at the restrictive temperature and treated with apoptosisinducing agents (Shi et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…HEK293 cells were seeded in 35-mm Petri dishes (5 Â 10 5 cells/ dish) the day before transfection with 0.1 mg of pEGFP-F (Harvey et al, 2000), 0.05 mg of pcDNA3 encoding Cterminally FLAG-tagged mature Omi and 2 mg of pCGN encoding N-terminally HA-tagged WARTS or WARTS(DVYV) (or the empty vector). After 24 h, the cells were fixed and stained with propidium iodide.…”
Section: Gst Pull-down Assays and Immunoprecipitationmentioning
confidence: 99%